2023
DOI: 10.3390/educsci13121222
|View full text |Cite
|
Sign up to set email alerts
|

Teacher Morale and Mental Health at the Conclusion of the COVID-19 Pandemic

Tim Pressley,
David T. Marshall,
Savanna M. Love
et al.

Abstract: As teachers entered the 2021–2022 school year, schools tasked teachers with the challenge of closing the learning loss gap, maintaining the same standards as a typical school year, implementing COVID-19 safety protocols and teaching to grade-level standards. The current study used the theoretical framework of teacher demoralization to explore teachers’ experiences of morale and mental health at the end of the 2021–2022 school year. The participants included 830 PK-12 individual teachers from across the United … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…Indeed, previous research has suggested that the work environmentincluding having a strong and supportive leadership team -is vital for staff retention (Sims, 2020). This has consequently led to renewed interest across the education sector in understanding working conditions within schools (Ladd, 2011;Kraft et al, 2021;Ravalier & Walsh, 2018) and the steps that can be taken to help improve collective staff morale (Benti & Tarekegne, 2022;Pressley et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, previous research has suggested that the work environmentincluding having a strong and supportive leadership team -is vital for staff retention (Sims, 2020). This has consequently led to renewed interest across the education sector in understanding working conditions within schools (Ladd, 2011;Kraft et al, 2021;Ravalier & Walsh, 2018) and the steps that can be taken to help improve collective staff morale (Benti & Tarekegne, 2022;Pressley et al, 2023).…”
Section: Introductionmentioning
confidence: 99%